OsPT4 Contributes to Arsenate Uptake and Transport in Rice - Ye, Ying; Li, Peng; Xu, Tangqian; Zeng, Liting; Cheng, Deng; Yang, Meng; Luo, Jie; Lian, Xingming (Frontiers in Plant Science, 2017)
Arsenic (As) is toxic to organisms, and elevated As accumulation in rice (Oryza sativa) grain may pose a significant health risk to humans. The predominant form of As in soil under aerobic conditions is As(V), which has a chemical structure similar to that of PO43-. Rice roots take up As(V) by phosphate (Pi) transporters, such as OsPT1 and OsPT8. In the present study, we investigated the contribution of OsPT4, belonging to the Pht1 family, on rice As(V) uptake and transport. We determined the mRNA amounts of OsPTs in rice seedlings, and expressions of OsPT1, OsPT4 and OsPT8 were up-regulated under As(V) conditions. OsPT4-overexpressing plants were obtained to examine the As (V) transport activity of OsPT4 in rice. When transgenic rice grew in hydroponic culture with 25 and 50 µM As(V), the plants showed sensitivity to As(V) stress with aboveground parts showing delayed growth and the roots stunted. The OsPT4 CRISPR lines showed the opposite phenotype. When plants were grown in 5 µM As(V) solution for 7 d, the As accumulation of OsPT4-overexpressing plants increased up to twice in roots and shoots. Furthermore, the arsenate uptake rates of OsPT4-overexpressing lines were higher compared with wild type. The Vmax of As(V) uptake in OsPT4-overexpressing plants increased 23-45% compared with Nipponbare. In the flooded soil, the As accumulation of OsPT4-overexpressing plants increased 40-66% and 22-30% in straw and grain respectively. While in OsPT4-cr plants As accumulation in roots decreased 17-30% compared with Nipponbare. Therefore, the present study indicates that OsPT4 is involved in As (V) uptake and transport and could be a good candidate gene to generate low As-accumulating rice.